Middle East Wars and The Refugee Crisis in Europe of the Last DeMiddle East Wars and The Refugee Crisis in Europe of the Last Decade: The Interaction of Islam and Post-Christian Civilization in the Westcade: The Interaction of Islam and Post-Christian Civilization in the West - Taivāne, Elizabete (History and Culture, 2023)
In his prominent and much-criticized book, “The Clash of Civilizations and the Remaking of World Order” (edited in 1996), Samuel Huntington claimed that the major civilizations were incompatible. For him so long as Islam remains Islam and the West remains the West, the fundamental conflict between the two great civilizations will continue to define their relations in the future. Now in the situation of the wars of the last decade a huge number of refugees from the Middle East has entered Europe bringing Islam with them. Was Huntington correct writing about the clash of Islam and the West or on the contrary is Western civilization now infected by Islam? Why doesn’t the West resist the Islamic culture? On the one hand it is easily giving up Christian values and on the other hand is not at all attracted by Islam. What is the religious situation in Europe at the present time and what guarantee may there be of European civilization surviving in the situation of the refugee crisis? Are there any parallels between the situation in European Union and that in Armenia? The present episode of interaction of civilizations is going to be discussed from the point of view of Religious Studies.